School Well-being in Terms of Self-Determination and Patience in Vocational High School Students - Abdillah, Hafizh Zain; Rahman, Fauzi; Husna, Muniratul; Sitinjak, Charli; Hidayah, Nurul; Mujidin, Mujidin (International Journal of Islamic Educational Psychology, 2022)
Previous research on school wellbeing has highlighted the need for its implementation in schools. This research aims to uncover two elements influencing school well-being: self-determination and patience. This study used quantitative methods with multiple linear regression analysis. The population in this study was 672 students of classes X, XI, and XII at SMK Muhammadiyah 1 Yogyakarta. The sampling technique employed in this study was cluster-random sampling with a sample of 178 students. The results showed an F-value of 27.182 with an absolute significance level (p-value) of 0.01, so the major hypothesis was accepted. The self-determination and patience variables simultaneously (together) could affect school well-being. The effect of self-determination on school well-being was 20%, while patience only contributed 3.67%. This research revealed (1) there was a positive influence of self-determination and patience on the well-being of vocational school students, (2) there was a positive effect of partial self-determination on school well-being, meaning that partial self-determination could predict school well-being, and (3) there was no partial positive effect of patience on school well-being, indicating that partial patience could not predict school well-being.